EFFECTIVENESS OF USING TRICHODERMA VIRIDE AS BIOSORBENT FOR REMAZOL BRILLIANT PURPLE IN BATIK WASTEWATER TREATMENT - Safitri, Anna; Febrianti, Wiwin Dwi; Rahmaniah, Galuh (JSMARTech, 2020)
Synthetic dyes used in the batik industry cause negative impacts to the environment. One type of synthetic dyes used in batik industry is remazol brilliant violet. This synthetic dye is reactive, carcinogenic, and non-biodegradable. Therefore, a strategy to degrade this synthetic dye is needed. In this study, the potential application of Trichoderma viride for biosorption of remazol brilliant violet (RBZ) in batik wastewater was investigated. The current work aimed on determination of the optimum biosorption conditions, including pH, contact time, and RBZ concentration. Biosorption of RBZ were carried out at pH 4 to 9; with contact times of 12, 24, 30, 36, and 42 h, with concentrations of dye solutions were 40, 60, 70, 80, and 90 mg/L. Results showed that the optimum biosorption of RBZ was obtained at pH 4, for 30 h, and optimum concentration of RBZ at 60 mg/L, with the RBZ absorbed was 79.27%. The FTIR analysis suggested that RBZ biosorption changed the chemical functional groups in the T. viride. The FTIR spectra revealed that the biomolecules that are affected during the process of biosorption were mainly lipids and proteins, and slightly from nucleic acids and carbohydrates.